An Appraisal Analysis of Attitude in Joko Widodo's ASEAN Summit Speeches - Sekarsari, Armita Ayu; Prastiwi, Yeny; Sutopo, Anam (VELES Voices of English Language Education Society, 2024)
This study employs Martin and White's (2005) Appraisal Framework to analyze the attitude subsystem within President Joko Widodo's speeches at the 2023 ASEAN Summit in Jakarta. The research focuses on uncovering the speaker's expressed attitudes by closely examining his language choices. Data was drawn from English translation scripts of speeches delivered on September 5-7, 2023, and selected using purposive sampling. Analysis of the 43rd ASEAN Summit reveals a significant emphasis on Affect, particularly Inclination, and expressions of Happiness and Satisfaction. Judgments of Veracity, Normality, and Capacity, though less frequent, were also present. The Appreciation category showcased a greater frequency of Reaction and Valuation, indicating the speaker's responsiveness to current challenges and articulation of long-term goals. Interestingly, the 26th ASEAN-Japan Summit speech exhibited a shift in emphasis. While the effect was still prominent, Judgment (precisely Capacity) and Appreciation became more pronounced. This suggests a heightened focus on highlighting expertise and shared values within the ASEAN-Japan context. Overall, this study offers insights into President Widodo's strategic use of language to convey attitudes, build consensus, and address regional issues. These findings have potential educational applications, demonstrating how language can reflect a speaker's beliefs and intentions.